2013
DOI: 10.1155/2013/285246
|View full text |Cite
|
Sign up to set email alerts
|

The Controversial Role of Microglia in Malignant Gliomas

Abstract: Malignant gliomas contain stroma and a variety of immune cells including abundant activated microglia/macrophages. Mounting evidence indicates that the glioma microenvironment converts the glioma-associated microglia/macrophages (GAMs) into glioma-supportive, immunosuppressive cells; however, GAMs can retain intrinsic anti-tumor properties. Here, we review and discuss this duality and the potential therapeutic strategies that may inhibit their glioma-supportive and propagating functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(172 citation statements)
references
References 132 publications
(100 reference statements)
2
168
0
2
Order By: Relevance
“…By secreting cytokines like IL-6, IL-10 and immune suppressive molecules, gliomas can polarize microglia into tumor supporting M2 phenotypes that participate in matrix remodeling and cell invasion. [125][126][127] In a recent study, PAM signaling was upregulated in microglial cells that were exposed to glioma derived factors, indicating that PAM signaling is needed to force microglial cells into a tumor supportive M2 state. [128] This result was supported by a report showing that mTOR inhibition with rapamycin polarizes microglia cells to express a tumor suppressive M1 phenotype.…”
Section: Pi3ks In Inflammation/ Microenvironmentmentioning
confidence: 99%
“…By secreting cytokines like IL-6, IL-10 and immune suppressive molecules, gliomas can polarize microglia into tumor supporting M2 phenotypes that participate in matrix remodeling and cell invasion. [125][126][127] In a recent study, PAM signaling was upregulated in microglial cells that were exposed to glioma derived factors, indicating that PAM signaling is needed to force microglial cells into a tumor supportive M2 state. [128] This result was supported by a report showing that mTOR inhibition with rapamycin polarizes microglia cells to express a tumor suppressive M1 phenotype.…”
Section: Pi3ks In Inflammation/ Microenvironmentmentioning
confidence: 99%
“…Microglia and bone-marrow-derived monocytes/macrophages have largely overlapping marker profiles and to date there is no unequivocal method to distinguish both cell types in samples resected from human GBM [162]. This matter is not trivial since monocytes of the peripheral blood and microglia have different developmental origin and may have distinct function in physiology and pathology [129].…”
Section: Microglia Developmentmentioning
confidence: 99%
“…Differential activation of STAT3 in TAM can control multiple immunosuppressive pathways in high-grade gliomas [162]. STAT3 activation in TAM is induced by different cytokines of the tumour microenvironment such as IL-10, IL-6, epidermal growth factor (EGF) and fibroblast growth factor.…”
Section: Adaptive Immune Functions In Gliomasmentioning
confidence: 99%
“…20,21 We therefore examined their roles in our GIC transplantation model. Using anti-IL12 p40 subunit and TNFa depletion antibodies, we found that neither factors had apparent effects on GIC elimination (Fig.…”
Section: Ecrg4 Prevented Gic Tumorigenesis Through the Activation Ofmentioning
confidence: 99%